A comparative study of philosophical courses syllabi in Macedonian and Croatian high schools - Dјeparoski, Ivan; Dimishkovska, Ana; Donev, Dejan; Popovska, Jasmina; Todorovska, Marija (Faculty of Philosophy, Skopje, 2019)
This paper outlines the general information about the subjects, the goals of the subjects, and the specifics of the contents in the subjects Philosophy, Ethics, Logic, and Aesthetics in the Republic of Macedonia and in the Republic of Croatia, in an attempt to provide a preliminary overview of the similarities and differences in the approaches to teaching these subjects. The program of the Republic of Croatia was selected for this review because of the positioning of the subjects within the high school curriculum, similar to the one in Macedonia (with a significant difference in the inclusion and representation of Ethics), as well as the general impression that these syllabi are most adapted to contemporary issues, and are the most context-sensitive.
Keywords: high school, syllabi, philosophy, Macedonia, Croatia